RECEPTION IN BASIC HEALTH CARE: CHALLENGES AND POSSIBILITIES FOR ITS IMPLEMENTATION AND CONSOLIDATION - Anselmo, Maria Elenir de Oliveira (2024)
Introduction: Reception is a light technology recommended by the National Humanization Policy. It constitutes one of the pillars of the structuring of Basic Health Care (BHC) and must be present in every care relationship. Objective: To analyze knowledge and perceptions of professionals who make up BHC teams about reception, identifying hindering and facilitating factors in the process of implementing and consolidating this tool. Method: This is a qualitative descriptive study. Data production was carried out through individual interviews with nine professionals (doctor – n=1, nurses – n=2, nursing technician – n=1, community health agents – n=2, oral health assistant – n =1, social worker – n=1 and manager – n=1), who make up the Family Health Strategy teams in a Health Unit in the city of Caxias do Sul, Rio Grande do Sul, Brazil. The interviews were recorded, transcribed and interpreted by content analysis, using the National Basic Care, Humanization and Permanent Health Education Policies as theoretical references. Results: Through the identification of three thematic categories generated, it was realized that there are still different perceptions regarding the real meaning of welcoming, and challenges and weaknesses that make its consolidation difficult. The relevance of Permanent Health Education was also highlighted, in addition to considering the social determinants that impact the health of the user/community, and the need for actions coordinated with other social facilities in the territory to strengthen reception. Conclusion: The implementation and consolidation of reception are challenges for ABS. It is necessary for teams to analyze how reception has been carried out and invest in possibilities that favor changes in work processes and that can contribute to strengthening reception and consequent increase in BHC’s resoluteness.